Inhibition of Swarming motility of Pseudomonas aeruginosa by Methanol extracts of Alpinia officinarum Hance. and Cinnamomum tamala T. Nees and Eberm. Issue 11 (3rd June 2018) - Lakshmanan, Divya; Nanda, Jishudas; Jeevaratnam, K.
Abstract: Bacterial drug resistance is a challenge in clinical settings, especially in countries like India. Hence, discovery of novel alternative therapeutics has become a necessity in the fight against drug resistance. Compounds that inhibit bacterial virulence properties form new therapeutic alternatives. Pseudomonas aeruginosa is an opportunistic, nosocomial pathogen that infects immune-compromised patients. Swarming motility is an important virulence property of Pseudomonas which aids it in reaching host cells under nutrient limiting conditions. Here, we report the screening of five plant extracts against swarming motility of P. aeruginosa and show that methanol extracts of Alpinia officinarum and Cinnamomum tamala inhibit swarming motility at 5 μg mL −1 without inhibiting its growth. These extracts did not inhibit swimming and twitching motilities indicating a mode of action specific to swarming pathway. Preliminary experiments indicated that rhamnolipid production was not affected. This study reveals the potential of the two plants in anti-virulence drug discovery. Abstract :